Judi Online di Kamboja dan Indonesia: Kegagalan ASEAN dalam Mencapai Interdependensi Negara Anggota - Darmawan, Gabriele Florecita; Winata, Valerie; Firdaus, Muhammad Andara (Jurnal Sentris, 2025)
ABSTRACT Online gambling is rising in Southeast Asian countries and poses a threat to the stability of a nation, both economically and socially, especially in Cambodia and Indonesia. Online gambling, a form of cybercrime that involves empty promises which is prevalent in Cambodia, has negatively impacted Indonesia’s economy and constructed a transnational threat to ASEAN countries. Certain factors cause the rise of this phenomenon, but the high prevalence of online gambling in Indonesia and Cambodia indirectly reflects the mechanization of Association of Southeast Asian Nations (ASEAN) as a regional institution. Even though various efforts and initiatives that ASEAN member countries have made to overcome the rise of online gambling, it can’t be denied that this transnational crime is ongoing between Indonesia and Cambodia. Therefore, this article aims to study how online gambling as a transnational crime can continue despite the presence of institutions such as ASEAN that aim to accommodate mechanisms such as regional cooperation with interdependence as an approach. Through qualitative research methods, this article shows the failure of ASEAN as an institution to achieve interdependence among its members to overcome the issue of online gambling in Southeast Asia, especially in Indonesia and Cambodia. Keywords: Transnational Crime; Online Gambling; Indonesia-Cambodia; ASEAN; Interdependence